A research agenda on Czech attitudinal perspectives in an era of digital transformation - Brunet-Thornton, Richard; Cramer, Tobias; Jirsák, Petr (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
This discussion centres on the growing impact of the transformation to digitalisation in various industry sectors. Enterprises seek to engage individuals who possess an appropriate profile to fulfil vacancies or new positions to assist in the transformation endeavour. Traditional job descriptions are replaced by the need for agile technical skills, project management competencies, and critical thinking. Challenges increase proportionally to the local employment rate. To evaluate such an impact, a project has been established to determine the reaction of employers once confronted with the lack of same-culture candidates. This manuscript represents the first phase of the project wherein the status quo is documented through an analysis of the extant literature. The findings of this exercise then serve as a benchmark from which survey results will be monitored. Although the literature review does not dispel all Czech stereotypes, it does provide a more realistic image of Czech cultural traits and characteristics.